Characterisation of Classical Sudden Infant Death Syndrome SIDS and Gray Zone SIDS in Japan Using Japanese Pathology and Autopsy Report 1982-1986 From the Japanese Society of Pathology - Sawaguchia, Toshiko; Fujitab, Toshiharu; Kobayashic, Makio; Sawaguchia, Akiko (The Bulletin of Legal Medicine, 1996)
There is no standardised criterion on the handling of Classical Sudden Infant Death Syndrome (SIDS) and Gray Zone SIDS. Particularly international discussion is needed on the handling of Gray Zone cases. Autopsy findings for Classical SIDS and Gray Zone SIDS in Japan has been analysed in preparing the basic data for this discussion in this report. The material analysed was found in the Japanese Pathology and Autopsy Report from the Japanese Society of Pathology (January 1982 to December 1986). A x2 test was required to find the difference between Classical SIDS and Gray Zone SIDS in each autopsy finding. In addition, factor analysis (the principal factor method with Varimax rotation) was carried out to identify the structure of the autopsy findings not only for Gray Zone SIDS but also for Classical SIDS. Using the x2 test a lymph tissue enlargement was found to have a high statistical value in Classical SIDS. Congestion, thymus enlargement, pulmonary oedema, adrenal gland atrophy, lymph tissue enlargement and neonate were recorded with .high factor loadings in Classical SIDS by factor analysis. Pneumonia, premature baby, and cardiomegaly was recorded with high statistical value in Gray Zone SIDS by the x2 test. Asphyxia, congestion, atelectasis, pulmonary emphysema, adrenal gland atrophy, premature baby, thymus hypoplasia, cardial malformation and ectopic hemopoesis were recorded as having high factor loadings in Gray Zone SIDS using factor analysis. Thymus enlargement and adrenal gland atrophy were recorded in the third factor of Gray Zone SIDS having rather high negative factor loading using factor analysis. It is remarkable that asphyxia was extracted in the first factor of Gray Zone SIDS with the highest loading factor using factor analysis. This fact might suggest indirectly that a percentage of Gray Zone SIDS would be underdiagnosed because of a substitutional diagnosis of asphyxia as being an external cause of death in Japan, even in general pathological autopsies during 1982 to 1986. Key Words: Sudden Infant Death Syndrome (SIDS), Classical SIDS, Gray Zone SIDS, Japanese Pathology and Autopsy Report, Factor Analysis